Evaluation of climate change adaptation in the energy generation sector in Colombia via a composite index — A monitoring tool for government policies and actions (2019)
The aim of the article is to evaluate the national adaptation to climate change in the energy generation sector in Colombia via a composite index. To build an index, a framework by stages is used, which includes the definition of the main concepts that supports the measurements; the selection of the relevant indicators using a subject matter experts; standardization of the indicators using a mathematic formula regarding the relationship between the variables that represent the adaptation to climate change; and establishment of the weights using an analytic hierarchical process of paired comparisons and the aggregation of indicators to obtain the following three sub-indexes: reactive adaptation, wherein the replacement of hydraulic energy by thermal energy is evaluated; anticipatory adaptation, which measures the gap between the generation of total energy and the demand of the national energy system; and planned adaptation, which considers indicators such as the sectoral plan for adapting to climate change, the law of alternative energies, and the generation of alternative energies as a percentage of generation capacity. By adding these sub-indices, the climate change adaptation index (CCAI) is obtained. The results of CCAI show that progress was made from a reactive adaptation scenario in which the system vulnerability was high to an anticipatory adaptation scenario wherein the vulnerability was average, indicating that the foundations for this sector to build a planned adaptation are currently being laid. © 2019